CULTIVATING CRITICAL THINKING ABILITY IN BTI IN CHINA - Yuehong Wei (University of Kuningan, 2018)
It is very vital for students in BTI to grasp the critical thinking ability, but how to cultivate this ability in the fundamental courses is a big problem to be solved. This study is to employ the teamwork, such as group discussion and group representation, and reflection log in the teaching process, investigating the dynamic situation through questionnaires. The results showed that group discussion, group presentation and reflection log are the effective ways to promote students’ critical thinking skills; however it cannot improve the critical thinking promptly in such a short time and it will be a successive process. Therefore, carrying out some class activities can enhance students’ critical thinking skills in English reading class.Keywords: BTI, English reading, critical thinking, teamwork, reflection log